About Between us - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
This new two-page section is Between us. Between you and CTA. Between CTA and you. And between you and other readers.How many people read Spore? It's hard to give an exact figure. We know that almost all the 26,000 copies of this Spore 80 were...